SURVEY FOR THE INCIDENCE AND SOURCES OF FIELD RESISTANCE AGAINST PEANUT BUD NECROSIS DISEASE OF GROUNDNUT IN NORTH EASTERN KARNATAKA - GURURAJ SUNKAD; BASAVARAJ NAGOJI; A. SRINIVASARAGHAVAN (The Bioscan, 2012)
Survey was conducted during kharif, 2007 and rabi/summer2007-08 revealed that the peanut bud necrosis disease (PBND) was prevalent in all groundnut fields in Upper Krishna Project (UKP) and TungaBhadra Project (TBP) areas. The disease incidence ranged from 1 to 44 during kharif and 1-84 per cent during rabi/summer. Over two seasons, the mean PBND incidence of 21.71, 18.23, 17.42 and 11.95 per cent was recorded in Raichur, Koppal, Gulbarga and Bellary districts, respectively. A diverse genetic material was screened against PBND at ‘hot spot’ centre during kharif, 2007 and rabi/summer, 2007-08. Thirteen entries viz., ICG -442, ICG-1668, ICG- 7906, ICG-9842, ICG-10185, ICG-11687, ICG-12000, ICG-12189, CS-92, CS-107, CS-205, R-2001-2 and R- 2001-3 showed consistent resistant reactionagainst the disease.